Оптимізація АЧХ пристрою звуковідтворення при дії акустичних завад - Кіселичник, М. Д.; Мелень, М. В.; Павлов, Ф. Б. (Видавництво Львівської політехніки, 2013)
The state standard for audio frequency amplifiers (LFA) requires the uniform amplitude-frequency characteristic (AFC) in the frequency range from 40 Hz to 18 kHz. But the test of high quality amplifiers on motor vehicles have shown that for the same output power verbal intelligibility is worse obtained than with simpler devices. This is because the that the main energy spectrum of speech is concentrated at frequencies up to 1 kHz, but at these frequencies it almost does not contain the information component, and in addition, is masked acoustic by noise which in most cases also dominates at low frequencies. Therefore, the main task of designing an amplifier that is intended for transmitting voice information, is reduced to the synthesis of optimal AFC by the criterion of maximum intelligibility of verbal message under conditions of acoustic noise. For a given full power of signal with a normal amplitude distribution and normal noise ratio with a specified energy spectrum the maximum speed of information transmission is provided for such energy spectrum of signal which having been added to the spectrum of the noise will ensure the constancy of this amount and its frequency independence, that has been clearly shown in the information theory. However, unlike the task discussed in information theory, the linguistic message is not noise-like. It is known that straight-articulation frequency bands, that frequency bands of the energy spectrum speech messages that equally influence on its intelligibility, differ significantly for width and increases with increasing a frequency. For this reason we introduced the concept of shown unit of bandwidth, also the energy spectrum of speech has been shown. In new terms of the criterion of maximum intelligibility of speech massage matches the criterion of maximum information speed transfer in the channels with noise-like signals and normal noise, that has allowed to find the optimal AFC of tract transmission coefficient – microphone – amplifier – speaker heads. Theoretical calculations have been found implementation in the development of transport loudspeaker device. Articulatory tests on the bus, which was carried out using tables of Ukrainian language, confirmed that the optimal AFC with downturn in the LF region with the steepness no less than 12 dB per octave makes it possible to increase verbal intelligibility of speech from 81 to 89%, or at the same intelligibility reduce output amplifier power to 3 times. The designed procedure of frequency dependence of the optimal tract sound transmission coefficient is suitable for any voice information transmission devices with limited average power under conditions of acoustic noise. Для випадку обмеженої вихідної потужності підсилювача низької частоти та в умовах дії акустичних шумів синтезована оптимальна амплітудно-частотна характеристика звукового тракту за критерієм максимальної розбірливості мовного повідомлення. Вводяться поняття про приведену одиницю смуги пропускання та приведений енергетичний спектр мови. У нових одиницях критерій максимальної розбірливості мовного повідомлення збігається з відомим критерієм максимальної швидкості передавання інформації в каналах із шумоподібним сигналом і нормальною завадою. На основі проведених розрахунків розроблено підсилювач низької частоти, призначений для використання в салоні автотранспортного засобу. Застосування в ньому запропонованої амплітудно-частотної характеристики дало змогу підвищити словесну розбірливість мови від 81 до 89% або зменшити вихідну потужність підсилювача втричі.
Optimization the AFC of sound reproduction device under the influence of acoustic noise
Keywords: low frequency amplifier (LFA); acoustic noise; information theory; speech intelligibility; the optimal amplitude-frequency characteristic (AFC) vehicles; підсилювач низької частоти (ПНЧ); акустичні завади; теорія інформації; розбірливість мови; оптимальна амплітудо-частотна характеристика (АЧХ); автотранспорт